Income Tax Calculation Analysis At IBP Bandung Tax Consultant Office - Pandu Adi Cakranegara; Ahmad Junaidi; Okevanrianus Okevanrianus; Dedy Suryadi; Rinjani Rinjani (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
In order to prepare corporate income tax at one of East Bandung's Accounting Services Offices, this research will look at the income tax article 21 computation using three ways (net, gross, and gross up). The study's focus is a business that offers services like bookkeeping, tax preparation, financial advice, and other related ones in Bandung. This study uses a qualitative approach method with additional quantitative information. The company's Article 21 PPh computation, salary information for permanent employees in 2022, and PPh regulations were all employed. The Gross Up method is the best and most effective method for business tax planning, according to the study's conclusions. The Gross Up strategy allows companies to offer tax incentives to their employees and can be used as a deduction from gross income, lowering the amount of corporate income tax owed. This study is only applicable to one company, and it can be developed by distributing questionnaires related to the article 21 income tax calculation calculation.